2021
DOI: 10.1371/journal.pone.0247898
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of depression, anxiety and associated factors among school going adolescents in Bangladesh: Findings from a cross-sectional study

Abstract: Background Common mental disorders in early life represent a major concern as they become more complex and intense with transition into adolescence. Despite global recognition of the significance of adolescent mental health, it remains a neglected area in research and health policy in Bangladesh. This study aimed to investigate the prevalence and factors associated with depression and anxiety among school going adolescents in Bangladesh. Methods A cross-sectional survey was conducted among 563 students aged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
21
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 43 publications
8
21
1
1
Order By: Relevance
“…In the present study, participants who did not engage in physical exercising compared to those who did were more likely to endorse anxiety and depression, similar to prior studies conducted in Bangladesh [ 39 , 56 , 59 , 62 ]. HCWs who smoked cigarettes were more likely to be anxious and depressed than non-smokers, also consistent with previous studies [ 63 66 ]. A pre-COVID-19 study among medical staff in Greece similarly showed significant associations with anxiety and depression [ 67 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study, participants who did not engage in physical exercising compared to those who did were more likely to endorse anxiety and depression, similar to prior studies conducted in Bangladesh [ 39 , 56 , 59 , 62 ]. HCWs who smoked cigarettes were more likely to be anxious and depressed than non-smokers, also consistent with previous studies [ 63 66 ]. A pre-COVID-19 study among medical staff in Greece similarly showed significant associations with anxiety and depression [ 67 ].…”
Section: Discussionsupporting
confidence: 91%
“…The present study revealed that anxiety and depression were strongly associated with each other ( r = 0.64). Anxiety and depression frequently co-occur [ 82 ], including in Bangladeshi groups [ 39 , 56 , 66 , 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, findings of the correlation analysis between the SAS and SDS standard scores showed that people with anxiety were likely to be depressed, and individuals with depression were also likely to be anxious which corroborate with earlier reports ( Islam et al., 2020 ; Islam et al., 2021 ; Islam et al., 2020 ; Islam et al., 2020 ; Kalin, 2020 ; Tasnim et al., 2021 ). Similar findings were found among Chinese people during the outbreak of COVID-19 (Y.…”
Section: Discussionsupporting
confidence: 90%
“…Responses were collapsed into a dichotomous form: good (i.e., excellent/very good/good) and fair/poor (i.e., poor/fair) (Ahmed et al, 2020 ). In addition, “yes/no” questions were asked during the survey with regard to physical exercise and current cigarette smoking (Islam et al, 2021 , 2021 , 2020 ; Rahman et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%